Breaking the taboo: An exploration of female university students' experiences of attending a feminist‐informed sex education course - Askew, Julie (Sex Education : Sexuality, Society and Learning, 2007)
This article presents the results of a qualitative interview study of nine young women who attended a feminist-informed human sexuality course as undergraduate students at a US university located in the "Bible belt". The course focused on messages of desire and empowerment, rather than romance or fear, and was designed to encourage students to think critically about current sexual discourses. Results indicate that participants' information on sexual issues prior to taking the course was limited and largely negative. Experiences of the course are described in themes including owning sexual desire, improved body image, reduced guilt and fear, and increased confidence as a woman. It is concluded that sex education may be used to help empower female students and enrich their quality of life; current educational practices should therefore be examined for ways in which they are oppressive to development.
Keywords: 2000-2009; amériques; discipline; image corporelle; jeunes femmes; pédagogie; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative

Mon/notre/leur corps est toujours un champ de bataille : discours féministes et queers libertaires au Québec, 2000-2007 - Breton, Émilie; Grolleau, Julie; Kruzynski, Anna; Saint-Arnaud-Babin1, Catherine (Recherches féministes, 2007)
Les auteures se livrent à une analyse des discours produits et diffusés par des groupes et des personnes qui luttent contre le patriarcat et l’hétérosexisme en priorité et qui semblent avoir une certaine culture libertaire. Une lecture des zines, des brochures, des journaux, des compilations vidéo/DVD, des albums de musique et des sites Web leur a permis de mettre en évidence trois tendances : la première regroupe les féministes radicales, clairement en continuité avec la génération politique précédente; la deuxième tendance s’apparente au women-of-color feminism; et la troisième est représentée par des groupes queers radicaux qui, tout en tentant de déconstruire l’identité sexuelle femme, invente un militantisme de multiples identifications.
Keywords: 2000-2009; 2000-2029; amériques; approches et analyses; corps; fem1000; hétérosexisme; militance; patriarcat; pratiques féministes; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; systèmes d'oppression; thématiques

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions